Determining the effectiveness of the physical therapy program for obese patients according to the dynamics of metabolic syndrome parameters - Mariia Aravitska (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to determine the effectiveness of the physical therapy program for obese patients by the dynamics of the components of the metabolic syndrome. Material & Methods: 214 people of the second adulthood with obesity I and II degree were examined. In terms of compliance, they were divided into a comparison group (low level) and a main group (high level). The control group consisted of 63 people without signs of obesity. The components of the metabolic syndrome were evaluated by anthropometric indicators (body mass index, waist and hip circumference, their ratio) and biochemical parameters (blood glucose, cholesterol, triglycerides, high density lipoproteins, leptin), and the visceral obesity index was calculated. The examination was carried out before and after the introduction of the annual program of physical therapy, which included maintaining a high level of compliance, increasing physical activity, changing the diet, reflexology, massage, and psychocorrection. Results: in all obese individuals were determined by abdominal obesity, fasting hyperglycemia and impaired glucose tolerance, high levels of total cholesterol, triglycerides, leptin, low levels of low-density lipoproteins. The visceral obesity index exceeded those of people with normal body weight (р<0,05). Compliance with the principles of the developed program made it possible to achieve a statistically significant (p<0,05) improvement relative to the initial indicators of all the studied parameters of the persons of the main group. Patients in the comparison group showed an increase in body mass index, a tendency to deteriorate atherogenic dyslipidemia and glucose uptake, a high content of leptin. Conclusions: as a result of the implementation of the developed program of physical therapy, a statistically significant improvement in the studied parameters of the metabolic syndrome in obese patients was compared with the initial result and the comparison group.